TEKNOLOGI BIOSOILDAM MA-11 UNTUK PENINGKATAN DAYA DUKUNG TANAH MARGEL PADA LAHAN TANAMAN JATI - Widiasmadi, Nugroho (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The objective of this analysis improvement of soil infiltration rate on margel land agroland for tectona grandis with involve biofertilizer MA-11 on the Biosoildam. As a control is original soil without microbial activity triggered. The research was use double ring infiltrometer to measure soil infiltration with three replication on each distance from Biohole and use electrolit conductivity meter (EC) to measure soil fertility by saltion consentration and soil acidity. The measurement was done in every five minute and observtian periode every fifteen days along fortyfive days. The result of research show that the highest of infiltration rate, infiltration capacit, fertility & acidity was happened on soil with involve Biofertilizer MA-11. The infiltration rate shows a constant value at the level of 500 to 725 cm / hour which is achieved after the 18th day. Meanwhile, the EC value in stable conditions is achieved on the 30th day with a value between 725 - 1000 uS/cm. So that the activity of biological agents on sand soil with an infiltration rate will be optimal on the 27th day.